SPECIFIC FEATURES OF THE ART OF ALLEGORY IN MODERN UZBEK STORYTELLING (Proceedings of International Educators Conference, 2024)
In the article, the poetic features characteristic of the prose of the new era, the use of artistic image tools, in particular, the art of allegory, were covered in detail. The unique aspects and unique situations of Shukur Kholmirzayev's stories were analyzed in the new era story-writing.